The use of Papacárie® as a stress control strategy in pediatric dentistry (Research, Society and Development, 2021)
Stress and anxiety is part of human behavior. It is a normal and healthy response by the child to a different situation. For this, behavior adaptation techniques, based on scientific principles, help the professional in conducting dental treatment. However, with the declaration of the World Health Organization about the disease pandemic caused by the new coronavirus (COVID-19), elective dental treatments were postponed and the dental routine was changed, also affecting the behavioral management. Based on this situation, the aim of this study was to carry out a narrative review of the literature on the use of Papacárie as a way of managing the behavior of children when returning to dental care. Knowing that this material is part of the minimally invasive technique for removing decayed tissue, facilitating the removal of infected dentin and ensuring the patient greater comfort when compared to the conventional method without the need for the use of anesthesia. Thus, after searching the Pubmed database and analyzing the articles, we concluded that when compared to the conventional method, the use of Papacárie in carious tissue presents less sensitivity during treatment, reduces the risk of pulp exposure and does not cause tissue damage. healthy. Therefore, when correctly indicated, the technique only improves dental care, the child's behavior and the acceptance of the patient and guardians, and can be an alternative in the first consultation as a way of treating and controlling the child's stress.